Potassium Ferrate (VI) as the Multifunctional Agent in the Treatment of Landfill Leachate - Thomas, Maciej (Materials (Basel), 2020)
Possible use of potassium ferrate (VI) (K(2)FeO(4)) for the treatment of landfill leachate (pH = 8.9, Chemical Oxygen Demand (COD) 770 mg O(2)/L, Total Organic Carbon (TOC) 230 mg/L, Total Nitrogen (Total N) 120 mg/L, Total Phosphorus (Total P) 12 mg/L, Total Coli Count (TCC) 6.8 log CFU/mL (Colony-Forming Unit/mL), Most Probable Number (MPN) of fecal enterococci 4.0 log/100 mL, Total Proteolytic Count (TPC) 4.4 log CFU/mL) to remove COD was investigated. Central Composite Design (CCD) and Response Surface Methodology (RSM) were applied for modelling and optimizing the purification process. Conformity of experimental and predicted data (R(2) = 0.8477, R(adj)(2) = 0.7462) were verified using Analysis of Variance (ANOVA). Application of K(2)FeO(4) using CCD/RSM allowed to decrease COD, TOC, Total N, Total P, TCC, MPN of fecal enterococci and TPC by 76.2%, 82.6%, 68.3%, 91.6%, 99.0%, 95.8% and 99.3%, respectively, by using K(2)FeO(4) 0.390 g/L, at pH = 2.3 within 25 min. Application of equivalent amount of iron (as FeSO(4) × 7H(2)O and FeCl(3) × 6H(2)O) under the same conditions allowed to diminish COD, TOC, Total N, Total P, TCC, MPN of fecal enterococci and TPC only by 38.1%, 37.0%, 20.8%, 95.8%, 94.4%, 58.2%, 90.8% and 41.6%, 45.7%, 29.2%, 95.8%, 92.1%, 58.2%, 90.0%, respectively. Thus, K(2)FeO(4) could be applied as an environmentally friendly reagent for landfill leachate treatment.